2020
DOI: 10.1038/s41467-020-15987-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural visualization of 3D chromatin folding using volume electron microscopy and DNA in situ hybridization

Abstract: The human genome is extensively folded into 3-dimensional organization. However, the detailed 3D chromatin folding structures have not been fully visualized due to the lack of robust and ultra-resolution imaging capability. Here, we report the development of an electron microscopy method that combines serial block-face scanning electron microscopy with in situ hybridization (3D-EMISH) to visualize 3D chromatin folding at targeted genomic regions with ultra-resolution (5 × 5 × 30 nm in xyz dimensions) that is s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…New methods of super-resolved optical reconstruction of chromatin organization with oligopaints technology 56 or the combination of serial block-face scanning electron microscopy with in situ hybridization (3D-EMISH) 63 have opened up new ways to explore the geometrical variability of TAD-like structures in comparison with TADs identified by ensemble Hi-C and to close current gaps of knowledge on nuclear compartmentalization. Despite compelling evidence for chromatin loops, their actual 3D and 4D (space-time) organization is not known.…”
Section: Discussionmentioning
confidence: 99%
“…New methods of super-resolved optical reconstruction of chromatin organization with oligopaints technology 56 or the combination of serial block-face scanning electron microscopy with in situ hybridization (3D-EMISH) 63 have opened up new ways to explore the geometrical variability of TAD-like structures in comparison with TADs identified by ensemble Hi-C and to close current gaps of knowledge on nuclear compartmentalization. Despite compelling evidence for chromatin loops, their actual 3D and 4D (space-time) organization is not known.…”
Section: Discussionmentioning
confidence: 99%
“…In the 3D-EMISH study, BAC-probes covering the 1.7-Mb region on chromosome 7 in lymphoblastoid GM12878 cells were detected with 1.4-nm-thick streptavidin-conjugated fluoronanogold, followed by analysis of density center distribution in reconstructed ultrastructural serial images of targeted chromatin region. While BAC-probes used in this study could not discriminate between three distinct CTCF-bordered loop domains, identified by ChIA-PET (Chromatin Interaction Analysis by Paired-End Tag sequencing) within this region, 3D-EMISH generally captured from one to four microscopically identified domains, which had highly variable structure and volume ( Trzaskoma et al, 2020 ). Similarly, imaging-based models of a single 13 kb loop and its 10 kb flanking regions in T-cell receptor alpha locus, probed by FISH and iPALM, showed multiple loop conformations in single cells.…”
Section: Fish-visualization Of Chromatin Domains In Model Organismsmentioning
confidence: 79%
“…Heterogeneity of chromatin-folding structures within distinct loop domains has also been demonstrated in human cell line by ISH combined with serial block-face scanning electron microscopy (3D-EMISH) ( Trzaskoma et al, 2020 ), FISH with interferometric PALM (iPALM; Jufen Zhu et al, 2019 ) and loop tracing with DNA-PAINT in non-denaturing conditions ( Beckwith et al, 2021 ). In the 3D-EMISH study, BAC-probes covering the 1.7-Mb region on chromosome 7 in lymphoblastoid GM12878 cells were detected with 1.4-nm-thick streptavidin-conjugated fluoronanogold, followed by analysis of density center distribution in reconstructed ultrastructural serial images of targeted chromatin region.…”
Section: Fish-visualization Of Chromatin Domains In Model Organismsmentioning
confidence: 99%
“…In the last decade the nucleus, which was a proverbial black box, has been unmasked as a highly dynamic, ultra-structured entity that is dynamically reforming based on biochemical cues from the microenvironment and mechanical cues from the tissue. This evolution of scientific understanding is in large part due to advances in light microscopy and new creative imaging techniques [179,180].…”
Section: Fluorescence Imaging Techniquesmentioning
confidence: 99%